2023
DOI: 10.1111/geb.13658
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the problem of scale that emerges with habitat fragmentation

Abstract: Fragmentation and scale Although habitat loss has well‐known impacts on biodiversity, the effects of habitat fragmentation remain intensely debated. It is often argued that the effects of habitat fragmentation, or the breaking apart of habitat for a given habitat amount, can be understood only at the scale of entire landscapes composed of multiple habitat patches. Yet, fragmentation also impacts the size, isolation and habitat edge for individual patches within landscapes. Addressing the problem of scale on fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…What are the mechanisms driving the effects in these experiments? There are several hypothesized mechanisms for the effects of habitat fragmentation and these mechanisms can operate at different scales (Fahrig et al, 2019; Fletcher Jr. et al, 2023). Previous results from Experiment 1 revealed that movement of C. vittiger was impeded with aggregated loss, leading to effects on local reproduction (Fletcher Jr., Reichert, & Holmes, 2018; Poli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…What are the mechanisms driving the effects in these experiments? There are several hypothesized mechanisms for the effects of habitat fragmentation and these mechanisms can operate at different scales (Fahrig et al, 2019; Fletcher Jr. et al, 2023). Previous results from Experiment 1 revealed that movement of C. vittiger was impeded with aggregated loss, leading to effects on local reproduction (Fletcher Jr., Reichert, & Holmes, 2018; Poli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Yet we expected that species with greater dispersal capacities would show weaker responses to habitat fragmentation than the poorer dispersers. In general, we expected that patch-scale responses would be consistent with landscape-scale responses, due to the interdependence of habitat patterns across scales (Fletcher Jr. et al, 2023). Despite this potential consistency, we expected that patch size alone would be helpful but not sufficient for predicting landscape-scale effects of habitat loss and fragmentation due to landscape-scale processes not being captured.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations